(3eONd aj GdGbJUGO GdEOGQj (B/s - (3GdUejOYj, eMehO LGSes; (3QOjfI ,YKeGf jhSas ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2006)
-(3GdfXQjGJ GdGbJUGOjI dOQGSI hJaSjQ Sdhc GdeSJgdc,Gdeaghe hGdGHYGO GdGbJUGOjI,GdQHM, GdJfHD HGdWdH,GdefGaSI,GdGfJGLjI,GdJcGdja,GdGYdGf,GdehGRfGJ GdJbOjQjI,GdQbGHI Ydi GdLhOI(B.s
(3GdeQGLY U(B.299s
Keywords: (3GdEOGQIs; (3GdGbJUGO GdEOGQjs; (3ChQGb GdCYeGds